IMPROVING VOCABULARY MASTERY USING VOCABULARY BUILDER APPLICATION ON THE SECOND SEMESTER STUDENTS' AT UNIVERSITAS BHINNEKA PGRI - Ika Rakhmawati (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2023)
We know that learning vocabulary is not easy. It needs long time to master vocabulary. Reality shows that if word is provided in the context, learning more concrete and fast because student has an understanding of whole. Phillips (in Kasihani 1995:74) “Both vocabulary and grammar need to be taught in context and the children should always be given plenty of opportunities to use the language that they have learned in class”. So, students will understand more easily in learning vocabulary if the context is associated with a child's world, so they can easilyput into practice or to communicate. So, many students have to master the vocabulary skills to improve their skills in English.The design of this research is a classroom action research with cycle model since this research is planned to improve the students’ Vocabulary mastery at the second semester of Universitas Bhinneka PGRI using Vocabulary Builder Application. Action research is a form of collective self-reflective enquiry undertaken by participants in social situations in order to improve the rationality and justice of their own social or educational practices, as well as their understanding of those practices and the situations in which the practices are carried out (Carr and Kemmis 1988: 5-6 in Smith, 2007). According to the result of Test Cycle I was done in cycle I, it was found that the students who could reach the passing grade were 17 students (81%) and 4 students (19%) were failed. The criteria of success which had been determined was 80% of the students and the standard value was 85. So, the action in cycle 1 was successful. The suggestion for the students by using Vocabulary Builder Application, the students can know much idiom, vocabulary mastey and it makes students more active in teaching and learning process, for English lecturer should use vocabulary builder Application as alternative way in teaching English and for future researcher as the reference to make a further research